2005
DOI: 10.1111/j.1542-474x.2005.00595.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Reperfusion on P‐Wave Duration and P‐Wave Dispersion in Acute Myocardial Infarction: Primary Angioplasty versus Thrombolytic Therapy

Abstract: Primary angioplasty reduces the incidence of AF by decreasing P max and P-wave dispersion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 22 publications
2
22
0
Order By: Relevance
“…Situations related to increased duration (and a tendency for atrial fibrillation) include hypertrophic cardiomyopathy [6], status post cardiac surgery [43], cardiac infarction and failure [15,39], increased left-atrial size and pressure [3], ischemic heart disease and exercise [29,35], as well as hypertensive and valvular heart disease, pericarditis, and dilated cardiomyopathy [8,42]. Coronary reperfusion following angioplasty can reshorten the P-wave and thus protect against atrial fibrillation [2]. In the light of the above, we should explain the possible rationale for any shortening or prolongation of atrial conduction time during laparoscopic operations, as expressed in the mean and maximal duration of the P-wave.…”
Section: Discussionmentioning
confidence: 99%
“…Situations related to increased duration (and a tendency for atrial fibrillation) include hypertrophic cardiomyopathy [6], status post cardiac surgery [43], cardiac infarction and failure [15,39], increased left-atrial size and pressure [3], ischemic heart disease and exercise [29,35], as well as hypertensive and valvular heart disease, pericarditis, and dilated cardiomyopathy [8,42]. Coronary reperfusion following angioplasty can reshorten the P-wave and thus protect against atrial fibrillation [2]. In the light of the above, we should explain the possible rationale for any shortening or prolongation of atrial conduction time during laparoscopic operations, as expressed in the mean and maximal duration of the P-wave.…”
Section: Discussionmentioning
confidence: 99%
“…Further investigations (49)(50) demonstrated that abnormal P-wave SAECG and atrial late potentials might be reduced by primary intervention during acute MI.…”
Section: Electrophysiological Associations Of Atrial Fibrillation Aftmentioning
confidence: 98%
“…P-wave duration and dispersion were compared in 72 MI patients undergoing primary PCI versus thrombolytic therapy (49). Akdemir et al have found that P-wave duration and dispersion significantly reduced only after primary PCI but not after thrombolytic therapy.…”
Section: Electrophysiological Associations Of Atrial Fibrillation Aftmentioning
confidence: 99%
See 1 more Smart Citation
“…P-wave dispersions and P-wave durations were significantly decreased after PTCA. In that study, primary PTCA reduced the incidence of AF by decreasing P max and P-wave dispersion [23]. …”
Section: Discussionmentioning
confidence: 99%